Early Modern Hate speechMartin Luther`s Anti-Semitism Responses and Reactions - Rudnick, Ursula (Cross currents, 2017)
The article examines German theologian, composer, priest, and monk Martin Luther's antisemitism, highlighting his role in Protestant Reformation. Topics include Luther's demonization of Jews and Judaism, his 1543 essay "On the Jews and their Lies," and his preoccupation with the Jews as a peripheral issue of his theological existence. Also explored are the influence of his antisemitic writings on Lutheran theologians and the ecclesiastic condemnation of his antisemitism.